Adaptation of Coastal Management Policy in Sustainable Tourism with Blue Economy Principles at PPP Mayangan - Nurul Jannah Lailatul Fitria; Sutarjo Sutarjo (Indonesian Tourism Journal, 2025)
Coastal fishing ports are increasingly expected to operate not only as landing and logistics nodes but also as local growth engines; however, tourism expansion around port areas can intensify waste, habitat degradation, and unequal benefit distribution, undermining blue economy targets. This study examines how the management and development of the Mayangan Coastal Fishing Port (PPP Mayangan) align with sustainable tourism and blue economy principles, and identifies key factors shaping that alignment. Using a qualitative descriptive approach, data were gathered through direct observation, in-depth interviews, and document/literature review. Purposive sampling involved eight informants: two officials from the PPP Mayangan technical unit, two local residents, two tourism operators, and two academics; fieldwork was conducted in August–September 2025. The analysis shows that PPP Mayangan’s sustainability orientation is expressed through conservation-based tourism (including mangrove-focused activities), efforts to reduce and manage waste and improve resource efficiency in fisheries-related tourism services, and collaboration among government, community, and private actors. Economically, tourism supports local value-added products and livelihoods; socially, community participation and cultural identity are leveraged to strengthen destination appeal; environmentally, conservation practices are treated as assets and safeguards. Overall, PPP Mayangan demonstrates that integrating coastal governance, stakeholder coordination, and conservation-driven attractions can operationalize blue economy principles, suggesting the need for consistent enforcement, capacity building, and integrated monitoring to sustain benefits over time for long-term coastal resilience.